Answer:
(4,-3)
Step-by-step explanation:
Easiest way to do this without any advanced methods is to use the answer choices to your advantage.
For a.) we have (1,1) meaning x = 1 and y = 1 if we get a 7 for the first equation and a -2 for the second equation then that is the correct answer.
Let x=1, y =1:
4(1)+3(1)=4+3=7 Correct so far.
1+2(1)=1+2=3 Incorrect since we should have got a -2 if this was the solution
Let (0,-1) x = 0, y = -1:
4(0) + 3(-1) = 0 -3 = - 3 Incorrect so we can stop there next answer choice.
Let (4,-3) x = 4 y = -3:
4(4)+3(-3)=16-9=7 Correct so far.
4+2(-3)=4-6=-2 Both are correct!
Therefore the solution (where the lines intersect) is (4,-3).
Answer: (A) SAS (B) No (C) SSS (D) No
<u>Step-by-step explanation:</u>
A) ET ≅ MT, ∠T ≅ ∠T, TA ≅ TA ⇒ Side-Angle-Side
B) top and base are congruent, diagonal is congruent to itself, but there is no way to prove that two angles are congruent without knowing if either of the sides are parallel.
C) JU ≅ JE, UN ≅ EN, JN ≅ JN ⇒ Side-Side-Side
D) angle-angle-angle only proves similarity, not congruency
Answer:
Step-by-step explanation:
![2x^6+17x^3+8 \\ = 2x^6+16x^3 + {x}^{3} +8 \\ = 2{x}^{3} ( {x}^{3} + 8) + 1( {x}^{3} + 8) \\ = ( {x}^{3} + 8)(2 {x}^{ 3} + 1) \\ = ( {x}^{3} + {2}^{3} )(2 {x}^{ 3} + 1) \\ = (a + 2)( {a}^{2} - 2a + {2}^{2} )(2 {x}^{ 3} + 1) \\ = (a + 2)( {a}^{2} - 2a + 4 )(2 {x}^{ 3} + 1) \\](https://tex.z-dn.net/?f=2x%5E6%2B17x%5E3%2B8%20%5C%5C%20%20%3D%202x%5E6%2B16x%5E3%20%2B%20%20%7Bx%7D%5E%7B3%7D%20%2B8%20%5C%5C%20%20%3D%20%202%7Bx%7D%5E%7B3%7D%20%28%20%7Bx%7D%5E%7B3%7D%20%20%2B%208%29%20%2B%201%28%20%7Bx%7D%5E%7B3%7D%20%20%2B%208%29%20%5C%5C%20%20%3D%20%28%20%7Bx%7D%5E%7B3%7D%20%20%2B%208%29%282%20%7Bx%7D%5E%7B%203%7D%20%20%2B%201%29%20%5C%5C%20%20%3D%20%28%20%7Bx%7D%5E%7B3%7D%20%20%2B%20%20%7B2%7D%5E%7B3%7D%20%29%282%20%7Bx%7D%5E%7B%203%7D%20%20%2B%201%29%20%20%5C%5C%20%20%3D%20%28a%20%2B%202%29%28%20%7Ba%7D%5E%7B2%7D%20%20-%202a%20%2B%20%20%7B2%7D%5E%7B2%7D%20%29%282%20%7Bx%7D%5E%7B%203%7D%20%20%2B%201%29%20%20%20%5C%5C%20%20%3D%20%28a%20%2B%202%29%28%20%7Ba%7D%5E%7B2%7D%20%20-%202a%20%2B%20%204%20%29%282%20%7Bx%7D%5E%7B%203%7D%20%20%2B%201%29%20%20%5C%5C%20)
Answer:
36
Step-by-step explanation:
Ejiro + her sister's age = 64
Ejiro is 8 years older so (64 - 8) ÷ 2 = 28 her sister is 28 years old and ejiro is 28 + 8 = 36 years old
Answer: The answer should be 0.125
Step-by-step explanation: